2016
DOI: 10.6018/analesps.32.2.208381
|View full text |Cite
|
Sign up to set email alerts
|

Influencia en la elección de modo de transporte de la información sobre variabilidad en el tiempo del viaje, beneficios personales y daño ambiental del coche versus transporte público

Abstract: Título: Influencia en la elección de modo de transporte de la información sobre variabilidad en el tiempo del viaje, beneficios personales y daño ambiental del coche versus transporte público. Resumen: En un estudio experimental, se examina la influencia en la elección de modo de transporte, para desplazarse al lugar de trabajo, de la información sobre la variabilidad del tiempo del trayecto, los beneficios personales o los daños ambientales de utilizar coche o transporte público. Además de estas variables, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that people base their selection decisions on the comfort, convenience, reliability and safety of the means of transportation (Barff et al , 1982). Several variables that affect mobility behavior are needed to understand what behaviors contribute to the traffic problem in cities (Steg and Gärling cited by López-Sáez et al , 2016). Gillen (1977) found that the higher the socio-economic level, the higher the value placed on the time savings provided by private transport.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies have shown that people base their selection decisions on the comfort, convenience, reliability and safety of the means of transportation (Barff et al , 1982). Several variables that affect mobility behavior are needed to understand what behaviors contribute to the traffic problem in cities (Steg and Gärling cited by López-Sáez et al , 2016). Gillen (1977) found that the higher the socio-economic level, the higher the value placed on the time savings provided by private transport.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…So we can say that the important determinants of entrepreneurial behavior are the personality traits that individuals have (Sánchez-García, 2010). It has been found that entrepreneurs have characteristic personality traits that predispose them to acting in an entrepreneurial manner, the most common traits are the Locus of Control, self-efficacy, risk and proactivity (Boada-Grau et al, 2016;Cromie, 2000;Vecchio, 2003). Tan (2001), in a study conducted with Chinese entrepreneurs, concluded that these entrepreneurs tend to be overly optimistic when they analyze environmental information, especially when they are not familiar with the problem and/or there is great uncertainty.…”
Section: Entrepreneurship Orientationmentioning
confidence: 99%